Cronica da cultura do rami em Uraí: lembranças de trabalhadoree, 1960-1980 - Cleuza Batista de Oliveira; Alessandra Babler Gusmão; Regina Célia Alegro (Confins)
This article highlights one of the most important stages in the history of the city of Uraí, peak production of ramie (Uraí bears the title of “capital of ramie”, although since the 1980s the fiber is no longer the main product of its economy). It presents information about the cultivation of ramie in northern Parana and emphasizes narratives of workers who describe their daily life sentence in ramicultura in the time.